2020
DOI: 10.21831/jpe.v8i2.34446
|View full text |Cite
|
Sign up to set email alerts
|

The problem-based learning e-module of planes using Kvisoft Flipbook Maker for elementary school students

Abstract: The conduct of the present study is encouraged by the needs to afford the teaching materials in the form of an electronic learning module or e-module that can be combined with the problem-based learning approach in order to expand the students’ insights in and draw the students’ interest toward Mathematics. These needs should be afforded because the present teaching materials used in the learning process are still conventional and, consequently, the students become easily bored. Departing from this elaboration… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
55
0
12

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 65 publications
(70 citation statements)
references
References 27 publications
3
55
0
12
Order By: Relevance
“…This is in line with the results of research showing the results of data analysis, the results of the feasibility test of electronic module media on material experts I and II can be concluded that the Electronic Module is feasible and effective for use in the learning process (Elder et al, 2019;Susanti et al, 2020). Second, the electronic module is structured with contextual examples with language that is easier to understand so that students are motivated to learn (Fonda & Sumargiyani, 2018;Triwahyuningtyas et al, 2020). Third, the modules are structured based on classroom learning consisting of learning outcomes and indicators, materials, concept understanding, summaries, practice questions, and self-reflection so that students can learn and measure their respective abilities.…”
Section: Resultssupporting
confidence: 81%
“…This is in line with the results of research showing the results of data analysis, the results of the feasibility test of electronic module media on material experts I and II can be concluded that the Electronic Module is feasible and effective for use in the learning process (Elder et al, 2019;Susanti et al, 2020). Second, the electronic module is structured with contextual examples with language that is easier to understand so that students are motivated to learn (Fonda & Sumargiyani, 2018;Triwahyuningtyas et al, 2020). Third, the modules are structured based on classroom learning consisting of learning outcomes and indicators, materials, concept understanding, summaries, practice questions, and self-reflection so that students can learn and measure their respective abilities.…”
Section: Resultssupporting
confidence: 81%
“…The importance of teaching materials in the learning process requires teachers to be able to develop teaching materials that are in line with the needs of learners, curriculum demands, not dependent on textbooks and government assistance package books, and in line with the characteristics of learners (Andani & Yulian, 2018;Mayarnimar & Taufina, 2017;Weriyanti et al, 2020). Appropriate teaching materials, curriculum, needs, and characteristics will increase student motivation, and learners can learn according to science and technology development (Irwansyah et al, 2017;Suzuki et al, 2020) In addition, teaching materials can increase the creativity of learners (Triwahyuningtyas et al, 2020;Tsai et al, 2017). So, the presence of quality teaching materials will impact the activity, interest, creativity that results in the learning outcomes of learners..…”
Section: Discussionmentioning
confidence: 99%
“…Previous research stated that E-modules could facilitate students 'learning (Tchen et al, 2018;Triwahyuningtyas et al, 2020). Other research findings also state that E-modules can attract students' attention to learning to become fun (Aprilia & Suryadarma, 2020;Rasmussen et al, 2020).…”
Section: Introductionmentioning
confidence: 90%